Crop Residue Management Initiatives in Changing the Farmers Behaviour and Farm Production in Bareilly district - Singh, B P; Singh, Madan; Kumar, Vijay; Reddy, M B; Chander, Mahesh; Shruti,; Suman, R S; Yadav, Vanee (Indian Journal of Extension Education, 2024)
The study was conducted in Bareilly District of Western Uttar Pradesh from 2022 to 2023 to ascertain the impact of In-situ Crop Residue Management (CRM) initiatives in changing the farmers’ behaviour and improving the farm production on farmers’ field. A total of 81 adopted farmers were selected purposively for the study. In-situ crop residue management increased from 13.6 to 92.6 per cent. Further, the manure and fertilizer usage in major crops viz. wheat, sugarcane, and mustard were reduced significantly among the adopted farmers on whose fields the demonstrations of crop residue management were conducted. The crop yield of wheat, mustard, and sugarcane increased significantly by 24.44, 42.48, and 18.31 per cent, respectively among the adopted farmers. Also germination, tillering/branching in plants, moisture in soil, and size of the grain increased due to the in-situ management of crop residue as reported by 70 to 80 per cent of the farmers. Adoption of crop residue management practices in wheat crop reduced the cost of cultivation by 4 per cent and gross and net return increased by 26.8 and 44.3 per cent, respectively.
Keywords: In-situ; Crop residue management; Farmers behaviour; Crop yield; Farm implements; Straw burning